Rodlet cells, fish immune cells and a sentinel of parasitic harm in teleost organs. Issue 121 (February 2022) - Sayyaf Dezfuli, Bahram; Pironi, Flavio; Maynard, Barbara; Simoni, Edi; Bosi, Giampaolo
Abstract: Rodlet cells (RCs) are the enigmatic and distinctive pear-shaped cells had found in many tissues of marine and freshwater teleosts. They have a distinctive fibrous capsule or the cell cortex that envelopes conspicuous inclusions called rodlets, basally situated nucleus, and poorly developed mitochondria. The contraction of the cell cortex results in the expulsion of the cell contents through an apical opening. One hundred and thirty years since rodlet cells were first reported, many questions remain about their origin and a function. This review will present new evidence regarding the relationship between RCs and metazoan parasites, and a protozoan infecting organs of different fish species, and update the state of knowledge about the origin, structure and the function of these intriguing fish cells. Highlights: Rodlet cells (RCs) are exclusive of teleost organs. Parasite elicits recruitment and increase of RCs in site of infection. RCs represent an inflammatory cell type closely linked to other innate immune cells. RCs could be potential biomarker for stressors and chemical agents.